קללת האהבה - הקנסיונרו של החטאים ואסון הסירנות: קריאה חדשה במר מאני לאברהם ב. יהושע - שי, אלי (מכאן, 2007)
Mr. Mani is to be considered the highest literary achievement in the novels of A.B. Yehoshua and its last chapter is to be considered the dramatic climax of the book. This chapter is an expression of the wish of the author to reconnect with his long-forgotten ethnic family roots of the Sephardic community in old Jerusalem, which were so vividly portrayed in a series of books by his father Jacob Yehoshua. However, beyond what might look, at first reading, as an emotional nostalgic yearning towards the roots of the family in the Ottoman period, there stands a constructed criminal code which hides the highly developed sinful mechanism of Abraham Mani, the main protagonist of this last chapter. A detailed analysis of the Ladino poem, “The cansionero of Esterrika who’s eyes are so lovely,” shows that this poem, sung by Mani in the midst of his confession to his Rabbi Hananyah Hadaya, is to be seen and heard not only as a soft musical interval in his tense monologue. Rather, it is a con- structed code that hides the singer’s four grave and deadly sins: his direct personal responsibility for the murder of his son Joseph, the incest he committed with Tamara, the widow of his son, his wish to tempt the wife of his Rabbi, Lady Flora and his attempt to end the life of the sick old Rabbi through the very power of his singing. In a much wider perspective, one can see behind this episode four patterns of the dramatic narrative, so typical of the novels of Yehoshua; the compulsive guest who is totally possessed by his idee fixe; The guest who strives to get into the bed of his host; the devoted care giver who attempts to kill the person he is treating; and the deadly singing, which is to be followed from the operatic odyssey of Molko in Berlin to the temptation of the troubadours in a Journey to the End of the Millenium. Thus, the literary creation of Yehoshua’s novels reconnects with the ancient motif of the dangerous singing of the Sirens, which originated in Greek mythology and was later a source of inspiration for Kafka. Strangely enough, although the works of Yehoshua have been analyzed in great detail, it seems that the most basic element in his main novels, represented by the four sins of Mr. Mani Abraham, have been totally ignored. This article tries to show that this repression is part of a much larger cultural censorship regarding the very essence of Jewish Sephardic poetic culture that hides provocative sexual content behind the traditional screen of the Romancero and the Cansionero.